Lactose azocalixarene drug delivery system for the treatment of multidrug-resistant pseudomonas aeruginosa infected diabetic ulcer - Li, Juan-Juan; Hu, Yuqing; Hu, Bing; Wang, Wenbo; Xu, Haiqi; Hu, Xin-Yue; Ding, Fei; Li, Hua-Bin; Wang, Ke-Rang; Zhang, Xinge; Guo, Dong-Sheng (Nature communications, 2022)
Diabetic wound is one of the most intractable chronic wounds that is prone to bacterial infection. Hypoxia is an important feature in its microenvironment. However, it is challenging for antimicrobial therapy to directly apply the existing hypoxia-responsive drug delivery systems due to the active targeting deficiency and the biofilm obstacle. Herein, we customizes a hypoxia-responsive carrier, lactose-modified azocalix[4]arene (LacAC4A) with the ability to actively target and inhibit biofilm. By loading ciprofloxacin (Cip), the resultant supramolecular nanoformulation Cip@LacAC4A demonstrates enhanced antibacterial efficacy resulting from both the increased drug accumulation and the controlled release at the site of infection. When applied on diabetic wounds together with multidrug-resistant Pseudomonas aeruginosa infection in vivo, Cip@LacAC4A induces definitely less inflammatory infiltration than free Cip, which translates into high wound healing performance. Importantly, such design principle provides a direction for developing antimicrobial drug delivery systems. Infection is a major issue in chronic diabetic wounds. Here, the authors report on a hypoxia triggered drug delivery system to achieve higher drug levels with controlled release to treat wounds infected with multidrug-resistant pseudomonas aeruginosa and demonstrate antibacterial and anti-biofilm action